Gallstones and Concomitant Gastric Helicobacter pylori Infection - UĞURLU, MUSTAFA ÜMİT (HINDAWI LTD, 2013)
Background. The association of gallstones with Helicobacter pylori has been investigated but not clearly demonstrated. In this study, the presence of H. pylori in the gallbladder mucosa of patients with symptomatic gallstones was investigated. Method. Ninety-four consecutive patients with symptomatic gallstone disease were enrolled for the study. Gastroscopy and gastric H. pylori urease test were done before cholecystectomy to all patients who accepted. After cholecystectomy, the gallbladder tissue was investigated in terms of H. pylori by urease test, Giemsa, and immunohistochemical stain. Results. Overall 35 patients (37%) gallbladder mucosa tested positive for H. pylori with any of the three tests. Correlation of the three tests Giemsa, IHC, and rapid urease test was significant (r(s): 0590, P > 0.001). Rapid urease test was positive in the gastricmucosa in 47 (58.7%) patients, and it was positive in the gallbladder mucosa in 21 patients (22%). In 15 patients both gastric and gallbladder tested positive with the urease test. There was significant correlation of rapid urease test in both of gallbladder and gastric mucosa (P = 0.0001). Conclusion. Study demonstrates the presence of H. pylori in the gallbladders of 37% of patients with symptomatic gallstones.
Keywords: GALLBLADDER TISSUE; DNA; BILE; ASSOCIATION; ANTIBODIES; ANTIGENS; CANCER